The Effect of Environmental, Social, and Governance (ESG) Disclosure on Market Returns - Annisa Salsabila; Fenny Marietza (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
The research aims to determine the effect of ESG Disclosure on Market Returns. The ESG Disclosure measurement was done using Environment Social Governance Disclosure Index, based on GRI 300 for the environment, GRI 400 for the social, and GRI 102 for the governance. The Market Returns measurement was done using absolute return and risk-adjusted return. The population in this study is IDXESGL companies listed on the Indonesia Stock Exchange for 2020-2021. The sample in this study is 16 companies (32 observations). The data analysis method used in this study was done with a simple - multiple regression analysis with the help of the E-views application. The study's findings show that information concerning ESG Disclosure is valuable for investors, indicating a company's emphasis on sustainable practices. This focus can contribute to enhancing their market return. This study implies that the results provide knowledge that the company should be able to disclose ESG information adequately, actively, and transparently in disclosing ESG information and implement sustainable business practices to gain a competitive advantage in the market.